2019
DOI: 10.1038/s41598-019-46879-1
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Evaluation of Possible Ganglion Cell Loss in the Retina of Zucker Diabetic Fatty (ZDF) Rats

Abstract: A thinning of the inner retina is one of the earliest potential markers of neuroretinal damage in diabetic subjects. The histological background is uncertain; retinal ganglion cell (RGC) loss and changes in the structure or thickness of the inner plexiform layer (IPL) have been suspected. Studies conducted on animal models on RGC pathology gave contradictory results. Hereby we present RGC numbers, distribution patterns and IPL thickness from Zucker Diabetic Fatty (ZDF) rats. After labelling RGCs on retinal who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…To address whether aberrant specification of neuronal subtypes or Müller glia in either Vglut1 -/- or Gnat1 -/- retinas may be responsible for the vascular phenotypes seen in these mutants, we immunolabelled and quantified the number of neuronal subtypes and Müller glia. There was no significant difference in the number of ganglion cells [NeuN + 41, 42 ], amacrine (except for a slight reduction in the Vglut1 -/- retina) and horizontal cells [Calbindin + 43 ], photoreceptors [measured by outer nuclear layer (ONL) thickness] among the three genotypes (Figure S5A-I) . Similarly, the number of Sox9 + Müller glia 44, 45 was similar among WT, Vglut1 -/- and Gnat1 -/- retinas (Figure S5J, K) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address whether aberrant specification of neuronal subtypes or Müller glia in either Vglut1 -/- or Gnat1 -/- retinas may be responsible for the vascular phenotypes seen in these mutants, we immunolabelled and quantified the number of neuronal subtypes and Müller glia. There was no significant difference in the number of ganglion cells [NeuN + 41, 42 ], amacrine (except for a slight reduction in the Vglut1 -/- retina) and horizontal cells [Calbindin + 43 ], photoreceptors [measured by outer nuclear layer (ONL) thickness] among the three genotypes (Figure S5A-I) . Similarly, the number of Sox9 + Müller glia 44, 45 was similar among WT, Vglut1 -/- and Gnat1 -/- retinas (Figure S5J, K) .…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted July 11, 2023. ; https://doi.org/10.1101/2023.07.10.548410 doi: bioRxiv preprint (Buckingham et al, 2008;Hajdu et al, 2019)], amacrine (except for a slight reduction in the Vglut1 -/retina) and horizontal cells [Calbindin + (Usui et al, 2015)], photoreceptors [measured by outer nuclear layer (ONL) thickness] among the three genotypes (Figure S5A-I). Similarly, the number of Müller glia, measured by Sox9 labeling (Poche et al, 2008;Serjanov et al, 2018) was similar among WT, Vglut1 -/and Gnat1 -/retinas (Figure S5J, K).…”
Section: Deep Plexus Angiogenesis Is Accelerated and Paracellular Brb...mentioning
confidence: 99%
“…However, other studies found no evidence of RGC loss, even under conditions of chronic hyperglycemia [24]. This discrepancy may be due to different RGC detection methods, their quantification, animal strains used, and the degree of hyperglycemia achieved in the different studies [25,26]. For example, Brn-3a has been reported to only detect RGC loss after a relatively longer duration of hyperglycemia as compared with the use of the neuronal biomarker NeuN [27].…”
Section: Discussionmentioning
confidence: 99%